2012
DOI: 10.1128/jvi.06230-11
|View full text |Cite
|
Sign up to set email alerts
|

The Highly Conserved Arginine Residues at Positions 76 through 78 of Influenza A Virus Matrix Protein M1 Play an Important Role in Viral Replication by Affecting the Intracellular Localization of M1

Abstract: Influenza A virus matrix protein (M1) plays an important role in virus assembly and budding. Besides a well-characterized basic amino acid-rich nuclear localization signal region at positions 101 to 105, M1 contains another basic amino acid stretch at positions 76 -78 that is highly conserved among influenza A and B viruses, suggesting the importance of this stretch. To understand the role of these residues in virus replication, we mutated them to either lysine (K), alanine (A), or aspartic acid (D). We could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 59 publications
4
28
0
Order By: Relevance
“…M1 in assembled virions functions as a bridge to interact with vRNP and the cytoplasmic tails of viral surface HA and NA (4,5,17,28,29). Consistent with the observation from the cellular membrane association experiment, the virions of M(NLS-88K), M(NLS-88E), and M(NLS-88V) showed a disrupted thin M1 layer under TEM.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…M1 in assembled virions functions as a bridge to interact with vRNP and the cytoplasmic tails of viral surface HA and NA (4,5,17,28,29). Consistent with the observation from the cellular membrane association experiment, the virions of M(NLS-88K), M(NLS-88E), and M(NLS-88V) showed a disrupted thin M1 layer under TEM.…”
Section: Discussionsupporting
confidence: 83%
“…Following infection, M1 is dissociated from vRNP to allow the latter to enter into the host nucleus for vRNA synthesis. Later, M1 also assists the nuclear export of newly formed vRNP and transports it to the cellular membrane for virion assembly and budding (5)(6)(7). Thus, M1 possesses multiple functions in support of virus replication cycles.…”
mentioning
confidence: 99%
“…The arginine triplet in position R76/77/78 was first described by Das et al . in 2012 in another influenza A strain and is highly conserved among influenza A and B viruses [22]. Mutation of one or two of the three arginine residues reduces virus production due to a budding defect, apparently caused by accumulation of M1-containing vesicles below the cell membrane [22].…”
Section: -Introductionmentioning
confidence: 99%
“…in 2012 in another influenza A strain and is highly conserved among influenza A and B viruses [22]. Mutation of one or two of the three arginine residues reduces virus production due to a budding defect, apparently caused by accumulation of M1-containing vesicles below the cell membrane [22]. To unravel the role of these basic residues in the late steps of the virus live cycle, we decided to further investigate the role of these two M1 basic domains in influenza A(H1N1)pdm09 virus assembly and release.…”
Section: -Introductionmentioning
confidence: 99%
“…It has been observed that M1 can form large assemblies in association with model and cellular membranes and that these clusters can reach diameters of around 100 nm (8,9). Furthermore, it is known that the association between M1 and lipids is driven mainly by electrostatic forces and that the protein interacts with negatively charged lipids, in particular with phosphatidylserine (PS) (6,7,10). More specifically, targeting of M1 to the PM of infected cells might rely on interactions with other viral proteins (e.g., M2 or HA) and/or lipid domains (5,(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%